Risk Factors of Death in Chronic Obstructive Pulmonary Disease (COPD) Patients at Dr. Soetomo General Academic Hospital, Surabaya, in 2019 - Hilmy Indra Wedhana; Arief Bakhtiar; Edward Kusuma; Alfian Nur Rosyid (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga)
Introduction: The distribution of death and risk factors in chronic obstructive pulmonary disease (COPD) patients varies according to disease severity. This study aimed to determine the risk factors of mortality in COPD patients.